Enhancing activity of β-lactam and fluoroquinolones antibiotics by artemisinin and its derivatives against MDR Escherichia coli - Ul Haq, Shahbaz; Wang, Ling; Guo, Wenzhou; Aqib, Amjad Islam; Muneer, Afshan; Saqib, Muhammad; Ahmad, Saad; Ghafoor, Muzafar; Iftikhar, Amir; Chen, Keyuan; Liang, Jianping (Frontiers in Veterinary Science, 2022)
Artemisinin and its derivatives had played a biocidal role in biomedical remedies, while they were expected to enhance the activity of antibiotics against multiple drug-resistant bacteria. The current study evaluated the interaction of Artemisinin (ART), dihydroartemisinin (DHA), artesunate (AS), and artemisinic acid (AA) with β-lactam and fluoroquinolones antibiotics against E. coli. Antibiotic strip test (E-test), Kirby Bauer's disc test (KB method), and broth microdilution method were adopted for susceptibility analysis, while the checkerboard method was applied to assess synergisms. ART, DHA, AS, and AA showed significantly enhanced antibacterial effects of β-lactam antibiotics against different strains of E. coli. The study showed ciprofloxacin to be most effective by presenting the least MIC (0.017125±0.0022 µg/mL) while oxacillin was least effective (MIC 256 µg/mL) against E. coli. 100%, 75, and 50% of isolates showed synergism of AA with penicillin G, ampicillin, and oxacillin, respectively. A remarkable reduction in MIC was noted in ampicillin combination of AA (-0.912±0.908 µg/mL) and ciprofloxacin in combination with AS (-0.901±0.893µg/mL). Artemisinin and its derivatives increased antibiotic accumulation within E. coli in a dose-dependent manner. The time-kill assay significantly reduced the bacterial number within 24 hours of incubation. The study thus concludes greater room for improvement in enhancing the efficacy of antibiotics if used with artemisinin and its derivatives.